Corporate Social Responsibility Disclosure by SENSEX Companies in India. (February 2014) - Bhatia, Aparna; Chander, Subhash
Economic and social performances are the two strong pillars of sustainable corporate growth. The companies in India are now showing a genuine interest in the upliftment of the stakeholders they serve. They have started giving Corporate Social Responsibility (CSR) a place in their overall strategies of growth. This paper studies the extent of CSR disclosure made by leading companies constituting BSE SENSEX in India. The disclosure practices of 25 of these companies have been studied for the year 2009–2010 by preparing a CSR Index. Content Analysis has been used. Company-wise score and item-wise score has been calculated. The results show that the CSR disclosure by the leading companies in India is low. The company-wise mean disclosure is just 31 per cent while the category-wise mean disclosure is 40.32 per cent. The category of 'Others' followed by 'Environment' and then 'Community Involvement' are the most well-disclosed areas.